Genotype-negative multiple endocrine neoplasia type 1 with prolactinoma, hyperparathyroidism, and subclinical Cushing’s syndrome accompanied by hyperglycemia: a case report - Kubo, Haremaru; Wada, Ryota; Sekikawa, Naohiro; Nomura, Yasuhisa; Yamada, Mutsuo; Inoue, Minoru; Hattori, Naoki; Yamazaki, Yuto; Sugimoto, Kazuhiro (Frontiers in Endocrinology, 2024)
Background: Multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant disorder, accompanied by multiple endocrine neoplasms of the parathyroid, pancreas, pituitary, and other neoplasms in the adrenal glands. However, in some cases, patients clinically diagnosed with MEN1 may be genotype-negative. Case presentation: A 56-year-old female was diagnosed with MEN1 based on a macroprolactinoma (19 mm in diameter), primary hyperparathyroidism, and a cortisol-producing adrenal adenoma, without a family history. At first appearance, she had a hemoglobin A1c of 12.0% and a fasting plasma glucose level of 16.3 mmol/L (294 mg/dL). She complained of headaches and had a history of prolactinoma at 28 years of age, with concomitant elevated prolactin 1102.0 μg/L (ng/mL). Insulin therapy was initiated for glucose management following the administration of an oral hypoglycemic agent. Additionally, cabergoline was initiated for due to the prolactinoma, resulting in a normalized prolactin level. Thereafter, medication for diabetes could be withdrawn. Subsequently, surgery was performed for primary hyperparathyroidism and the cortisol-producing adrenal adenoma, which was consistent with the preoperative diagnosis. Additionally, a thyroid tumor resected with primary